1997
DOI: 10.1128/mcb.17.2.954
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Expression of Hel-N1, an RNA-Binding Protein, Increases Glucose Transporter (GLUT1) Expression in 3T3-L1 Adipocytes

Abstract: 3T3-L1 preadipocytes ectopically expressing the mammalian RNA-binding protein Hel-N1 expressed up to 10-fold more glucose transporter (GLUT1) protein and exhibited elevated rates of basal glucose uptake. Hel-N1 is a member of the ELAV-like family of proteins associated with the induction and maintenance of differentiation in various species. ELAV proteins are known to bind in vitro to short stretches of uridylates in the 3 untranslated regions (3 UTRs) of unstable mRNAs encoding growth-regulatory proteins invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

11
174
2

Year Published

1997
1997
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(188 citation statements)
references
References 44 publications
11
174
2
Order By: Relevance
“…HuR (8) is a ubiquitously expressed member of the embryonic lethal abnormal vision (ELAV) family of RNA-binding proteins (9). Three other closely related neural proteins, called HelN1 [or HuB (10,11)], HuC (11) and HuD (12), are target antigens in paraneoplastic neuropathy [Hu syndrome (13)]. HuR is a 36-kDa polypeptide that contains three classical RNA-binding domains [RNA recognition motifs (RRMs)] (8): the first two have been implicated in ARE recognition, whereas the third has been suggested to bind the poly(A) tail of target mRNAs (14).…”
Section: Hur Binding To Cytoplasmic Mrna Is Perturbed By Heat Shockmentioning
confidence: 99%
“…HuR (8) is a ubiquitously expressed member of the embryonic lethal abnormal vision (ELAV) family of RNA-binding proteins (9). Three other closely related neural proteins, called HelN1 [or HuB (10,11)], HuC (11) and HuD (12), are target antigens in paraneoplastic neuropathy [Hu syndrome (13)]. HuR is a 36-kDa polypeptide that contains three classical RNA-binding domains [RNA recognition motifs (RRMs)] (8): the first two have been implicated in ARE recognition, whereas the third has been suggested to bind the poly(A) tail of target mRNAs (14).…”
Section: Hur Binding To Cytoplasmic Mrna Is Perturbed By Heat Shockmentioning
confidence: 99%
“…Moreover, UV cross-linking experiments revealed that two smaller proteins with sizes of 36 and 45 kDa interacted with the poly(U) [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] eCPE. In this report, we show that the 36-kDa species, the only one that is cytoplasmic, is ElrA (10).…”
Section: Discussionmentioning
confidence: 99%
“…The ElrA sequence and expression pattern are also conserved in mammals (22,26). Members of the ELAV family interact with an AU-rich element in the 3Ј UTRs of several cytokine and other mRNAs and, at least in the case of human cells, have been implicated in the control of cell growth and differentiation, perhaps by influencing the degradation of such messages (1,7,17,21,22,24).In this report, we show that the 36-kDa eCPE-binding protein and ElrA are the same protein. Although ElrA specifically…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The Hu proteins have three highly homologous RNA-recognition motifs, the second and third separated by a less conserved stringer region (Szabo et al, 1991). HuD and Hel-N1 bind in vitro to AU-rich elements in the 3'-untranslated regions (3'-UTR) of mRNAs Gao et al, 1994;Jain et al, 1997;King et al, 1994;Levine et al, 1993;Liu et al, 1995). Other proteins binding AUrich sequences have been shown to destabilize mRNAs encoding growth-regulatory proteins (Brawerman, 1989;Sachs, 1993;Shaw and Kamen, 1986), participate in the regulation of RNA splicing (McCullough and Schuler, 1993;Singh et al, 1995), and transport messages from the nucleus (Muller et al, 1992).…”
Section: Introductionmentioning
confidence: 99%